2018
DOI: 10.1016/j.envres.2018.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled burning of solid waste by households in Mexico is a significant contributor to climate change in the country

Abstract: Uncontrolled burning of municipal solid waste (MSW) is an important source of air pollution and is wide spread in many developing countries, but only limited data quantify the extent of domestic open burning of household waste. Here, we present some of the first field data to be reported on the uncontrolled domestic burning of waste. A representative community of Mexico (Huejutla de Reyes Municipality) was investigated and household surveys, interviews with waste operators and a waste characterisation analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 18 publications
1
34
1
1
Order By: Relevance
“…It has estimated that about 8,882 tons of waste are burned per year, producing 1.97 kg BC t −1 , 11.9 kg PM 10 t −1 , and 9.8 PM 2.5 t −1 that contributed for 17.5 t BC y −1 (38,553 t CO 2 -eq per year), 105.7 t PM 10 y −1 and 87.0 t PM 2.5 y −1 , for a total of 313.7 kg CO 2 -eq y −1 per capita. The results showed that the CO 2 -eq from BC emitted by waste open burning was more than 15 times larger compared to CH 4 potentially released from the decomposition of equivalent amounts of combustible organic waste deposited at the dumpsite [76]. In another study, it was found that the majority of PM generated by waste open burning had smaller sizes (PM 1 ) compared to PM 2.5 and to PM 10 .…”
Section: Environmental and Social Issues Due To Sw Mismanagementmentioning
confidence: 99%
“…It has estimated that about 8,882 tons of waste are burned per year, producing 1.97 kg BC t −1 , 11.9 kg PM 10 t −1 , and 9.8 PM 2.5 t −1 that contributed for 17.5 t BC y −1 (38,553 t CO 2 -eq per year), 105.7 t PM 10 y −1 and 87.0 t PM 2.5 y −1 , for a total of 313.7 kg CO 2 -eq y −1 per capita. The results showed that the CO 2 -eq from BC emitted by waste open burning was more than 15 times larger compared to CH 4 potentially released from the decomposition of equivalent amounts of combustible organic waste deposited at the dumpsite [76]. In another study, it was found that the majority of PM generated by waste open burning had smaller sizes (PM 1 ) compared to PM 2.5 and to PM 10 .…”
Section: Environmental and Social Issues Due To Sw Mismanagementmentioning
confidence: 99%
“…The supplement for this article describes a list of known inventory issues at the time of submission, as well as a number of additional CEDSGBD-MAPS details, tables and figures, and data sources, including the following: (Boden et al, 2016(Boden et al, , 2017BP, 2015;Doxsey-Whitfield et al, 2015;EC-JRC/PBL, 2012EIA, 2019;IEA, 2015;Klein Goldewijk et al, 2011;Sharma et al, 2019;Stohl et al, 2015;The World Bank, 2016;UN, 2014UN, , 2015Wiedinmyer et al, 2014;Commoner et al, 2000;Reyna-Bensusan et al, 2018;Nagpure et al, 2015;Meidiana and Gamse, 2010;US EPA, 2006).…”
Section: Information About the Supplementmentioning
confidence: 99%
“…14,116 Consequently, black carbon may have as much as 5,000 times the global warning potential of carbon dioxide. 39 Two studies 81,82 identified in this review calculated emissions factors for plastic wastes (Table 8). However, both are of limited use for extrapolation, because the waste sources used are either unspecified in the case of Park et al 81 or highly specific in the case of Wagner et al 82 .…”
Section: Bisphenol a (Bpa)mentioning
confidence: 99%